Performance evaluation on mitral valve motion feature tracking using Kanade-Lucas- Tomasi (KLT) algorithm based eigenvalue measurement - Mahadi, Lina Farhana; Ibrahim, Nabilah; Zaluwi, Mohd Thariq; S.M Johan, Muhammad Haniff (AIP, 2019)
This paper provides the explanation of the concepts of point tracking technique to be implemented in mitral valve locating in video frames. Object tracking has been used for many applications in motion-based recognition and monitoring. This paper discussed about the implementation of Kanade-Lucas-Tomasi (KLT) algorithm for automatic detection of the mitral valve in video frames. An experiment is carried out which covers the patient scanning who suffers from mitral valve disease. The performance of the method is validated by comparing the value of point track per frames. It is found that the point tracker systems can track the mitral valve up to 0.3s.